Changes in innate and adaptive immunity over the first year after the onset of type 1 diabetes - Klocperk, Adam; Petruzelkova, Lenka; Pavlikova, Marketa; Rataj, Michal; Kayserova, Jana; Pruhova, Stepanka; Kolouskova, Stanislava; Sklenarova, Jana; Parackova, Zuzana; Sediva, Anna; Sumnik, Zdenek (Acta diabetologica, 2020)
AIMS: The development of the immune phenotype in patients with type 1 diabetes (T1D) during the first year following disease onset remains poorly described, and studies analysing the longitudinal development of a complex set of immunological and metabolic parameters are missing. Thus, we aim to provide such complex view in a cohort of 38 children with new onset T1D who were prospectively followed for 1 year. METHODS: All subjects were tested for a set of immunological parameters (complete blood count; serum immunoglobulins; and T, B and dendritic cells), HbA1c and daily insulin dose at baseline and at 6 and 12 months after T1D diagnosis. A mixed meal tolerance test was administered to each of the subjects 12 months after diagnosis, and the C-peptide area under the curve (AUC) was noted and was then tested for association with all immunological parameters. RESULTS: A gradual decrease in leukocytes (adjusted p = 0.0012) was reflected in a significant decrease in neutrophils (adjusted p = 0.0061) over the post-onset period, whereas Tregs (adjusted p = 0.0205) and originally low pDCs (adjusted p < 0.0001) increased. The expression of the receptor for BAFF (BAFFR) on B lymphocytes (adjusted p = 0.0127) markedly increased after onset. No immunological parameters were associated with C-peptide AUC; however, we observed a linear increase in C-peptide AUC with the age of the patients (p < 0.0001). CONCLUSIONS: Our study documents substantial changes in the innate and adaptive immune system over the first year after disease diagnosis but shows no association between immunological parameters and residual beta-cell activity. The age of patients remains the best predictor of C-peptide AUC, whereas the role of the immune system remains unresolved.
Keywords: Partial remission; Immunity, Innate; Adaptive Immunity; Humans; počet leukocytů; dítě; kohortové studie; C-Peptide; Child; Female; C-peptid; lidé; Leukocyte Count; mladiství; B-lymfocyty; Glycated Hemoglobin A; Cohort Studies; předškolní dítě; diabetes mellitus 1. typu; ženské pohlaví; Male; adaptivní imunita; Insulin; Insulin-Secreting Cells; Adolescent; B-Lymphocytes; Type 1 diabetes; regulační T-lymfocyty; C-peptide; beta-buňky; T-Lymphocytes, Regulatory; věk při počátku nemoci; mužské pohlaví; prospektivní studie; Age of Onset; Child, Preschool; glykovaný hemoglobin; přirozená imunita; Immune system; Diabetes Mellitus, Type 1; inzulin; Glycated Hemoglobin; Prospective Studies